MAIN CHARACTERISTICS AND COMPOSITION OF INNOVATIVE DEVELOPMENT IN THE WORLD ECONOMY (Ta'limning zamonaviy transformatsiyasi, 2024)
In the contemporary global economy, innovative development has emerged as a key driver of economic growth and competitiveness. This abstract aims to explore the main characteristics and composition of innovative development within the world economy. It delves into the essential elements defining innovative development, including technological advancements, research and development initiatives, entrepreneurial activities, and adopting new business models. The abstract also examines the role of innovation in fostering sustainable economic progress, addressing societal challenges, and creating opportunities for diverse stakeholders. By analyzing the composition of innovative development, this abstract seeks to provide insights into the evolving dynamics of the world economy and the critical factors shaping its future trajectory.